Bioclickable Mussel-Derived Peptides With Immunoregulation for Osseointegration of PEEK - Zhao, Huan; Wang, Xiaokang; Zhang, Wen; Wang, Lin; Zhu, Can; Huang, Yingkang; Chen, Rongrong; Chen, Xu; Wang, Miao; Pan, Guoqing; Shi, Qin; Zhou, Xichao (Frontiers in Bioengineering and Biotechnology, 2021)
Poly-ether-ether-ketone (PEEK)-based biomaterials have been widely used in the field of spine and joint surgery. However, the lack of biological activity limits its further clinical application. In this study, we synthesized a bio-clickable mussel-derived peptide Azide-DOPA4 as a PEEK surface coating modifier, and further combined bone morphogenetic protein 2 functional peptides (BMP2p) with a dibenzylcyclooctyne (DBCO) motif through bio-orthogonal reaction to obtain the DOPA4@BMP2p-PEEK. As expected, more BMP2p can be conjugated on PEEK after Azide-DOPA4 coating. The surface roughness and hydrophilicity of the DOPA4@BMP2p-PEEK were obviously increased. Then we optimized the osteogenic capacity of PEEK substrates. In vitro, compared with the BMP2p-coating PEEK material, the DOPA4@BMP2p-PEEK showed significantly higher osteogenic induction capability of rat bone marrow mesenchymal stem cells. In vivo, we constructed a rat calvarial bone defect model and implanted PEEK materials with differently modified surface. Micro-computed tomography scanning displayed that the DOPA4@BMP2p-PEEK implant group had significantly higher new bone volume and bone mineral density than the BMP2p-PEEK group. Histological staining of hard tissue further confirmed that the DOPA4@BMP2p-PEEK group revealed a better osseointegration effect compared to the BMP2p-PEEK group. Importantly, we also found that DOPA4@BMP2p coating has a synergistic effect with induced Foxp3+ regulatory T (iTreg) cells to promote osteogenesis. In summary, with an easy-to-perform, two-step surface bioengineering approach, the DOPA4@BMP2p-PEEK material reported here displayed excellent biocompatibility and osteogenic functions. It will, moreover, offer insights to engineering surfaces of orthopaedic implants.